Development of Kahoot Evaluation Tool Based on Mobile Learning in Economic Lessons for 10 Graders of SMA Negeri Taruna Nala Jawa Timur - Suseno, Wahyu Rizki Aris; Handayani, Sri (Classroom Action Research Journal (CARJO), 2020)
The purpose of this research and development is to develop Kahoot evaluation tools based on mobile learning in economy class X subjects of Taruna Nala High School in East Java. The research method used is the method of research development (research development) according to Borg & Gall with 7 stages consisting of 7 steps that have been approved. The results of this study indicate that the Kahoot evaluation method based on Mobile Learning that was developed included in the criteria suitable for use in the learning process with a total percentage of 90.33%.